2022
DOI: 10.5187/jast.2021.e128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperthermia on cell viability, amino acid transfer, and milk protein synthesis in bovine mammary epithelial cells

Abstract: Effect of hyperthermia on cell viability, amino acid transfer, and milk protein synthesis in bovine mammary epithelial cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Our results show that HS similarly impacts both differentiated (D) and undifferentiated (UD) cells, disrupting protein folding and RNA metabolism and downregulating solute carrier family 7, member 5 ( SLC7A5 ), an essential amino acid transporter for milk synthesis 44,45 . Downregulation of SLC7A5 was also observed in undifferentiated MAC-T cells 15 and in dairy cows 10 under HS. In addition, we found that HS repressed transfer RNA cysteine ( TRNAC - ACA ) and BarH like homeobox 1 ( BARHL1 ), which are related to milk yield and fat percentage, respectively 46,47 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our results show that HS similarly impacts both differentiated (D) and undifferentiated (UD) cells, disrupting protein folding and RNA metabolism and downregulating solute carrier family 7, member 5 ( SLC7A5 ), an essential amino acid transporter for milk synthesis 44,45 . Downregulation of SLC7A5 was also observed in undifferentiated MAC-T cells 15 and in dairy cows 10 under HS. In addition, we found that HS repressed transfer RNA cysteine ( TRNAC - ACA ) and BarH like homeobox 1 ( BARHL1 ), which are related to milk yield and fat percentage, respectively 46,47 .…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies using MAC-T cells under HS conditions have primarily focused on their undifferentiated state. For example, expression of HSP genes and apoptosis-related genes was significantly upregulated in undifferentiated MAC-T after HS treatment 14 , whereas baseline expression of milk protein genes was downregulated 15 . Recent work employing RNA-seq and methylated RNA immunoprecipitation sequencing (MeRIP) profiled transcriptomics and N6-methyladenosine (m6A) modification of HS undifferentiated MAC-T cells 16 , revealing upregulated expression of heat shock factor 1 ( HSF1 ), heat shock protein 70 ( HSP70 ), and apoptosis-related genes, and altered m6A modifications within genes in TGFβ, Wnt, and Hippo signaling pathways.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation